Desenvolvimento de um plug-in para a contagem de pontos por função no software Astah - Mori, Allan Victor (2015)
Conducting an effective planning software is critical to their development, it is necessary to estimate, measure and control: time, cost and complexity. It needs to go beyond the idealization in diagrams for execution, following standards of quality and grounded developing software architectures, which make the project has met its specified functionality. Another important point to the success of a softwares projects, is to comply with the deadline, in this context is considered the use of techniques to estimate software size. This work presents a tool that automates the recording of Function Points in a project created in the UML modeling program, Astah Professional, which is used to engineer software systems. The Astah allows the development of Java-based plug-ins, making use of the Eclipse development environment.